'Rauisuchian' material from the lower Elliot Formation of South Africa and Lesotho: Implications for Late Triassic biogeography and biostratigraphy. (December 2019) - Tolchard, Frederick; Nesbitt, Sterling J.; Desojo, Julia B.; Viglietti, Pia; Butler, Richard J.; Choiniere, Jonah N.
Abstract: 'Rauisuchians' are non-crocodylomorph pseudosuchian archosaurs that played important roles in terrestrial Triassic ecosystems. Because they are generally considered to have gone extinct in the end-Triassic mass extinction, they are potentially useful for relative dating of terrestrial strata. Despite the abundance of fossils of this group in South America, East Africa and Laurasia, there is currently no published definitive rauisuchian fossil record from southern Africa. However, several fragmentary archosaurian remains representing potential members of this grade have been recovered from the latest Triassic lower Elliot Formation of southern Africa. Here, we critically review this material and show that it represents a modest diversity of rauisuchians. These records are the southernmost palaeolatitudes that these animals are known to have occurred and the first definitive remains from southern Africa. Highlights: We identify fossils of 'rauisuchians' from South Africa's Elliot Formation. This is the first record of large carnivores from the lower Elliot Formation. The five specimens represent at least two distinct taxa. They are among the youngest and highest palaeolatitude record of the group. This research provides insight into the Late Triassic ecosystems of South Africa.